Strengthening Climate-Resilient Agricultural Systems in South Asia: CCAFS South Asia Regional Meeting Report - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
State of the art discourse on agriculture and climate change, lays emphasis on the dual role of agriculture in adapting to and mitigating climate change. Recognising the same, many countries are laying emphasis on agriculture while preparing their national adaptation plans (NAPs). In congruence with the world’s agenda to facilitate sustainable agricultural practices, while reducing poverty and hunger, CCAFS has been working for last 10 years to generate innovative solutions to promote more adaptable and resilient agriculture and food systems. South Asia regional office of Climate Change Agriculture and Food Security (CCAFS) has been: generating research based knowledge, mainstreaming climate variability and climate change issues into development strategies and institutional agendas; enhancing people's understanding of climate change issues; and facilitating informed decisions on policies and actions based on the best available information and data in India, Nepal and Bangladesh, with extended research and knowledge based services extended onto Bhutan and Sri Lanka. With the vision of drawing learnings from the work done so far to elucidate the strategy of the coming years, a regional meeting titled “Strengthening Climate-Resilient Agricultural Systems in South Asia” was organised by CCAFS- South Asia in Bali- Indonesia from 6th to 7th Oct 2019. The meeting also aspired to build as well as further strengthen already existing institutional partnership. The two-day agenda included thematic sessions on topics such as developing and evaluating alternative policy and institutional models for scaling-up climate smart food system in South Asia, big-data analytics to identify and overcome scaling limitations to climate-smart agricultural practices in South Asia, capacity building for scaling up CSA via South- South collaboration among others. The meeting culminated with an agreement on the need for revisiting CCAFS research approach to build science based evidence, to facilitate formulation of better policies and programs, for a food secure world.